Field identification of roots of woody plants of the savanna ecosystem study area, Nylsvley - M. C. Rutherford (Bothalia: African Biodiversity & Conservation, 1980)
A key for the field identification of fresh root material of 21 woody plant species on the savanna ecosystem study area, Nylsvley, South Africa, is given. Descriptions of macroscopic features of roots as well as photographic descriptions of roots and root systems are provided.